Efficient phosphate sequestration for water purification by unique sandwich-like MXene/magnetic iron oxide nanocomposites. Issue 13 (10th March 2016) - Zhang, Qingrui; Teng, Jie; Zou, Guodong; Peng, Qiuming; Du, Qing; Jiao, Tifeng; Xiang, Jianyong
Abstract : The ultrafine nano-Fe2 O3 particles aim to intercalate into the interior layers of MXene, increasing the number of available activated layers, which can achieve efficient phosphate removal in water. Abstract : Rationally tailored intercalation for two-dimensional (2D) layered MXene materials has aroused extraordinary enthusiasm for broadening their applications. Herein, a novel sandwiched structural 2D MXene-iron oxide (MXI) material, prepared by selectively exfoliating an Al layer followed by magnetic ferric oxide intercalation, exhibits remarkable applicability to trace phosphate sequestration in the environmental remediation realm. Compared with commercial adsorbents, the resultant MXI nanocomposite exhibits a fast separation in 120 s together with the superior treatment capacities of 2100 kg and 2400 kg per kg in simulated and real phosphate wastewater applications, respectively. Such efficient sequestration is ascribed to the formation of a unique nano-ferric oxide morphology. The ultrafine nano-Fe2 O3 particles can intercalate into the interior layers of MXene, widening the layer distance, and stimulating the available overlapping activated layers; while the efficient phosphate removal can be achieved by the strong complexation onto the embedded magnetic nano-Fe3 O4 with a unique sandwich-structure as well as the stimulated Ti–O terminal within MXene. Apart from the fact that this approach suggests a complementary means for environmental remediation, it opens a new trajectory to achieve the functionalization of MXene.